692 THE USE OF ULTRASOUND ENHANCING AGENTS (UEA) IN THE EVALUATION OF LEFT ATRIAL APPENDAGE (LAA) THROMBUS IN PATIENT CANDIDATE TO PERCUTANEOUS LAA CLOSURE. (15th December 2022) - Roccabruna, Alessandra; Fanti, Diego; Bonvicini, Eleonora; D´onghia, Giovanni; Sarao, Emanuele; Guarracini, Fabrizio; Bonmassari, Roberto; Luciano Ribichini, Flavio
Abstract: Introduction: Left atrial appendage closure (LAAC) is an emerging option in patients with atrial fibrillation (AF) and contraindication for oral anticoagulation (OAC) therapy. Patients with left atrial thrombus are usually excluded from this strategy. Therefore, pre-procedural transesophageal echocardiography (TEE) is usually performed for LAA thrombus exclusion. The application of second-generation lipid microspheres ultrasound enhancing agents (UEA) is of growing interest. The following clinical cases reports describe the benefit from UEA implication on subsequent decision-making regarding with LAAC procedure. Case report num.1: an 88-year-old male with history of symptomatic AF and post – traumatic cerebral bleeding was referred to LAAC because of high risk of bleeding in using OAC. Transthoracic echocardiography (TTE) documented a severely dilatated left atrium and preserved left ventricular systolic function. Pre – operative TEE revealed a " chicken wing " shaped LAA with severe spontaneous echo-contrast and sludge effect. Echo-contrast medium " SonoVue " showed an early filling defect with late but complete LAA opacification, excluding thrombus. Of note, ECG-gated cardiac CT (CCT) could not exclude filling defect with certainty. Consecutively, the patient was candidate to LAAC in a short time. Case report num.2: a 75-year-old man with valvular permanent AF and multi-territory ischemic ictus despite being on adequate prophylactic OAC (Warfarin). At TTE a dilated left ventricle with mildly reduced ejection fraction was documented. ECG – gated CCT with delayed phases imaging showed a possible filling defect in LAA, however imaging was suboptimal due to a reverb of voluminous hiatal hernia. TEE revealed a " windstock " shaped LAA with incomplete distal opacification when echo-contrast medium " SonoVue " was used, confirming thrombus. The patient was therefore referred for LAAC procedure with concomitant use of cerebral embolic protection devices (CEPDs). Discussion: Transesophageal echocardiography is the test of choice for the exclusion of LAA thrombus. However technical difficulty, spontaneous echo contrast (SEC) and prominent pectinate musculature within the appendage may make the exclusion of LAA thrombus not easy. ECG – gated cardiac CT may be conclusive as well. UEA use is associated with higher diagnostic power for LAA thrombus exclusion and recent study have shown its utility also in terms of LAA sizing. Thus, the most recent guidelines of American Society of Echocardiography mention echo contrast use for the delineation of LAA thrombi and differentiate between them with SEC. Conclusion: The use of ultrasound enhancing agents is useful and increases the interpretative confidence in exclusion of LAA thrombus.